Effects of hydroxypropyl-β-cyclodextrin on pyrene and benzo[α]pyrene: bioavailability and degradation in sotil. Issue 6 (3rd July 2018) - Liu, Tingfeng; Ding, Keqiang; Guo, Guang; Yang, Feng; Wang, Lihong
ABSTRACT: Effect of hydroxypropyl-β-cyclodextrin (HPCD) on the bioavailability and biodegradation of the polycyclic aromatic hydrocarbons (PAHs) pyrene (PYR) and benzo[ α ]pyrene (BaP) in spiked soils was investigated in 14-week incubation experiments. To evaluate the effect of HPCD in soils with a different matrix, humic substance (HS) was added into soil samples. A 6-h Tenax TA extraction method was used to evaluate pollutants bioavailability. The biodegraded and extracted fractions were compared to evaluate the impact of HPCD on PAHs biodegradation. Results indicated positive effects of HPCD on fast desorption behaviours of PAHs. The biodegraded fraction was consistent with that of the extracted for PYR. However, in terms of BaP, the results were contrary which suggests that biological factors may be limiting factors for BaP pollution remediation. HS weakened the HPCD solubilisation effect while accelerated the decay of PYR and BaP, also implying that bioavailability was not the sole factor limiting PAH biodegradation. In addition, analysis of microbial communities demonstrated that HPCD inhibited the growth of some soil bacteria while HS promoted the evolution of some soil microorganisms. A limited population of hydrocarbon degrader populations led to observing incomplete PAH biodegradation even in the presence of HPCD.